A generalized Bogomolov–Gieseker inequality for the smooth quadric threefold. (24th June 2014) - Schmidt, Benjamin
Abstract : We prove a generalized Bogomolov–Gieseker inequality as conjectured by Bayer, Macrì and Toda for the smooth quadric threefold. This implies the existence of a family of Bridgeland stability conditions.